Treve. - Terhune, Albert Payson, 1872-1942. (New York, Grosset & Dunlap, 1961)
A pedigree collie becomes a sheep dog loyally serving two ranchers whose ages and personalities are distinctly different.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Ranch life -- Fiction